Focal mechanism study of the Chakwal Earthquake of July 16, 2001 in the light of regional tectonics - Khan, Karam; Khan, Shahid A.; Qaisar, M. (Journal of Himalayan Earth Sciences, 2002)
On July 16, a body wave magnitude 5.2 (Ms 4.7) earthquake occurred near Chakwal, about 75 kin south of Islamabad. The earthquake was widely felt from Peshawar to Lahore. The fault-plane solution on the basis of P-wave polarity data of seismic stations of the PAEC's (Pakistan Atomic Energy Commission) Seismic Network has been found well-controlled and comparable with the Centroid Moment Tensor Solution given by Harvard University. The fault plane is oriented in the WNW direction with strike, dip and slip of 303o, 66o and 148o respectively Which is in accordance with the local tectonics of the region. On the basis of Focal Mechanism Solution of this earthquake, along with two more solutions of earthquakes of the region, a possibility of another subsurface fault parallel to the Kallar Kahar fault is also derived.